A mother’s management of rectal prolapse in a Nigerian toddler - Joel-Medewase, Victor Idowu; Onigbinde, Michael Olaniyan; Oyedeji, Olusola Adetunji (International Journal of Contemporary Pediatrics, 2017)
A 20 months old Nigerian girl who had rectal prolapse was subjected to sitting on a hot ‘sitz’- like bath as a home management of the prolapse. Gluteal, perineal and upper thigh burns and sepsis; also, febrile convulsion and spontaneous passage of 5 ascaris worms were the sequellae.